Anxiety-induced sleep disturbances among in-school adolescents in the United Arab Emirates: Prevalence and associated factors - Supa Pengpid; Karl Peltzer (Wolters Kluwer Medknow Publications, 2022)
Introduction: The goal of the study was to estimate the prevalence of anxiety-induced sleep disturbance (AISD) and assess its relationship with psychosocial distress, socio-environmental variables, and health risk indicators among adolescent schoolchildren in the United Arab Emirates (UAE). Methods: Cross-sectional data from the 2016 UAE "Global School-Based Student Health Survey" (n = 5849) were analyzed. The nationally representative sample of all students in grades 8-12 in the UAE was selected through a two-stage cluster sampling procedure. Schools were included with probability proportional to enrollment size, and classes were randomly selected, with all students present in selected classes being eligible to participate. Results: The overall prevalence of AISD was 16.2%, 11.9% had AISD among males, and 20.5% had AISD among females. In adjusted logistic regression analysis, older age (16 years or older), lower economic status (hunger), loneliness, frequent bullying victimization (10-30 days), frequently physically attacked (≥6 times), parental emotional neglect, parents never check homework, parental disrespect of privacy, passive smoking on all past 7 days, sedentary behavior (>8 h/day) during leisure time, and multiple (≥4 times) injuries were positively and being male was negatively associated with AISD. Conclusion: Almost one in six participants reported AISD, and several factors associated with AISD were identified.